APA Handbook of Clinical Geropsychology, Vol. 2: Assessment, Treatment, and Issues of Later Life. 2015
DOI: 10.1037/14459-026
|View full text |Cite
|
Sign up to set email alerts
|

Elder abuse and neglect.

Abstract: The problem of elder abuse comes to a geropsychologist's attention in a variety of ways. It may be that during a therapy session an older adult reveals he or she has been victimized, although he or she may not even recognize it as such. Or, a perpetrator of abuse may reveal he or she has been an abuser, again without recognizing it as such. Geropsychologists may be asked to examine an elder to determine their cognitive capacity to have made a decision in the past, such as entering into a marriage or signing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Psychologists and others working in clinical practice often struggle with identifying whether an older client has experienced abuse and when to report suspected abuse (Mosqueda & Olsen, 2015). To date, there is no single gold-standard test to ascertain abuse, with numerous tools employed by both researchers and clinicians.…”
Section: Detection Of Elder Abusementioning
confidence: 99%
See 3 more Smart Citations
“…Psychologists and others working in clinical practice often struggle with identifying whether an older client has experienced abuse and when to report suspected abuse (Mosqueda & Olsen, 2015). To date, there is no single gold-standard test to ascertain abuse, with numerous tools employed by both researchers and clinicians.…”
Section: Detection Of Elder Abusementioning
confidence: 99%
“…Moreover, the reliability and validity of most of the measures identified has yet to be established (Cooper, Selwood, & Livingston, 2008). Taking a more informal approach, Mosqueda and Olsen (2015) suggested that psychologists and other health care providers ask their older clients whom they suspect may be involved in an abusive situation a series of questions (e.g., “Are you afraid of anyone?” or “Is anyone mistreating you?”) . The client’s response will help clinicians determine the need to report suspected abuse or to pursue another course of therapeutic action (Zeranski & Halgin, 2011).…”
Section: Detection Of Elder Abusementioning
confidence: 99%
See 2 more Smart Citations